Neurogenesis in the Adult Brain II Clinical Implications - Seki, Tatsunori; Sawamoto, Kazunobu; Parent, Jack M.; Alvarez-Buylla, Arturo (Springer Japan : Imprint: Springer, 2011)
The discovery of adult neurogenesis caused a paradigm shift in the neurosciences. For more than 100 years, it was believed that adult neurons do not regenerate. Joseph Altman and Fernando Nottebohm found proof to the contrary and changed the course of history. Their research, included here, provides the foundations of the field. Today, adult neurogenesis is a rapidly expanding discipline applicable to the study of brain development and diseases, learning and memory, aging, and neuropsychiatric disorders. With multiple authors, the 27 chapters of this book contain the latest work in two volumes. The first presents the basic biology of adult neurogenesis in non-mammalian vertebrates and in the mammalian hippocampus and olfactory bulb, and the second discusses clinical implications and delves into adult neurogenesis and brain injury as well as neurodegenerative and neuropsychiatric pathologies. With details of the anatomy, physiology, and molecular biology of the two neurogenic brain regions, this book provides indispensable knowledge for many areas of neuroscience and for experimental and clinical applications of adult neurogenesis to brain therapy.